COST OF CAPITAL DERIVED FROM LONG TERM DEBT - Isdawati; Deddy Surachmad; Dewi Agustina; Gana Vige Ortega; Indrayani; Damsar; Muammar Khaddafi (PT. Radja Intercontinental Publishing, 2023)
Company capital that is used from debt has a greater risk than the capital owned by the company itself. The company's capital used must be done optimally in order to minimize financial risks that can occur. The capital structure determines the use of debt by financial managers to fund company activities. Decisions on capital structure (capital structure) include the selection of sources of funds both from own capital and foreign capital in the form of debt. In this case, capital becomes an important element for the running of a strategic business where the company needs to conduct a study and determine the size of the company's needs and ability to provide capital to support the work or business that will be carried out.